Influencing Factors of Postgraduates’ Online Learning Satisfaction: A Case Study of a Public University in Chongqing, China - Chen, Yanli (ABAC ODI JOURNAL Vision. Action. Outcome, 2023)
With the rapid development of information technology, online teaching has become a tradition of country-wide education. The widespread use of online instruction in colleges and universities still needs to improve in terms of student satisfaction, especially in Chongqing, China. The influencing factors of student satisfaction have been discussed in this study, including self-efficacy, perceived usefulness, ease of use, information quality, system quality, and service quality. Questionnaire was distributed to 500 postgraduate students from Southwest University of Chongqing, China. The Item-Objective Congruence (IOC) and pilot test (n=50) of Cronbach’s Alpha were validated before the data collection. Confirmatory factor analysis (CFA) and structural equation modeling (SEM) are the main statistical methods. Self-efficacy has a significant influence on perceived usefulness. Satisfaction is significantly influenced by perceived usefulness, perceived ease of use, information quality, service quality, and system quality. In conclusion, universities should organize regular seminars and workshops for lecturers on using mobile technology effectively to facilitate effective research and collaboration.